Approach to Examine the Effect of Atomic Number on Single – Electron System of Group III Elements - Ukpaka C.P.; Abraham Peter Ukpaka; Victor Chukwuemeka Ukpaka (International Journal of Crystalline Materials, 2024)
This study investigates the ionization energy, kinetic energy, and mass relationships among Group III elements (Boron, Aluminum, Gallium, Indium, and Thallium) to provide a comprehensive understanding of their atomic and physical properties. A detailed analysis of ionization energy trends reveals that Boron exhibits the highest ionization energy, while Thallium has the lowest, consistent with periodic trends influenced by increasing atomic radius and electron shielding. Gallium deviates slightly from this trend due to the presence of d-electrons, which contribute to additional shielding and reduced nuclear attraction. Further analysis of the kinetic energy-velocity relationship demonstrates that higher effective nuclear charge (Zeff) leads to increased electron kinetic energy, supported by quantum mechanical principles. Additionally, comparisons of atomic radius reveal that as atomic number increases, the balance between nuclear charge and shielding effects leads to varying spatial distributions, with Boron having the most compact electron cloud among these elements. Despite significant differences in atomic mass, the kinetic energy across these elements remains approximately constant, owing to the dominance of electron mass over atomic mass in determining kinetic behavior. This observation holds even in heavier elements like Thallium, where relativistic effects are minimal in this model. The study's findings align with existing literature on atomic behavior, providing new insights into the dynamics of Group III elements. It underscores the importance of electron configuration, shielding effects, and relativistic contributions in shaping their physical properties, reinforcing the accuracy of theoretical models in predicting atomic trends.
Keywords: Ionization energy trends; electron shielding and effective nuclear charge; group III elements; mass relationship; periodic properties and atomic behavior